2016
DOI: 10.1016/j.jpsychires.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of white matter in personality traits and affective processing in bipolar disorder

Abstract: Our findings showed important potential links between personality, affective processing and WM integrity in BD. In the future therapeutic interventions for BD using brain stimulation protocols might benefit from the use of DTI to target pathways underlying abnormal affective processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…We did however observe a negative cross-sectional effect of the CE factor on the cingulate-cingulum FA in both the full and HC subsamples, and the right cingulate-cingulum in the HC only, so that higher CE was associated with reduced white matter integrity as indicted by FA. The association of the cingulate with different personality traits such as neuroticism has been previously demonstrated in young and middle age adulthood with cross-sectional analyses ( Xu and Potenza, 2012 ; Bauer et al, 2016 ; Prillwitz et al, 2018 ; Sanjari Moghaddam et al, 2020 ). This could suggest that this personality-brain association is an indication of a lifetime stable trait, as opposed to arising as a consequence of aging.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We did however observe a negative cross-sectional effect of the CE factor on the cingulate-cingulum FA in both the full and HC subsamples, and the right cingulate-cingulum in the HC only, so that higher CE was associated with reduced white matter integrity as indicted by FA. The association of the cingulate with different personality traits such as neuroticism has been previously demonstrated in young and middle age adulthood with cross-sectional analyses ( Xu and Potenza, 2012 ; Bauer et al, 2016 ; Prillwitz et al, 2018 ; Sanjari Moghaddam et al, 2020 ). This could suggest that this personality-brain association is an indication of a lifetime stable trait, as opposed to arising as a consequence of aging.…”
Section: Discussionmentioning
confidence: 88%
“…With regards to the mechanistic links between personality and the aging brain, there are several points to consider. Personality traits have been cross-sectionally associated with several brain networks in adulthood, notably involving the prefrontal and cingulate regions ( Xu and Potenza, 2012 ; Bauer et al, 2016 ; Prillwitz et al, 2018 ; Sanjari Moghaddam et al, 2020 ). Certain acquired brain lesions or neurodegenerative diseases of these regions lead to personality changes and disturbances, as in the case of head trauma or frontotemporal degeneration ( Salloway et al, 2008 ; Rascovsky et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a higher number of single-nucleotide polymorphisms of the brain-expressed protocadherin 17 gene showed correlations with both impaired cognition and higher N. Increased gene expression was found in individuals with BD compared to HCs [52]. Another study suggested a negative correlation between N and reaction time in the Affective Go/No-Go paradigm with a bias towards affective stimuli, which was not significant in HC and might suggest a greater receptivity to emotional stimuli in individuals with BD [53].…”
Section: Introductionmentioning
confidence: 96%
“…For instance, fractional anisotropy (FA) can be used to estimate axonal myelination, axonal diameter, or fibre density ( Basser, 1997 ; Dennis et al., 2021 ). Several human neuroimaging studies have reported associations, both phenotypic and genetic, between dMRI microstructure measures and human traits (e.g., Bauer et al., 2016 ; Cox et al., 2016 ; Gray et al., 2020 ; Lu et al., 2018 ; Rutten-Jacobs et al., 2018 ). Given rodent evidence implicating the subiculum– BNST connection in HPA-axis modulation ( Herman et al., 2020 ), white matter microstructural properties of this tract may be related to traits and behaviours associated with stress reactivity.…”
Section: Introductionmentioning
confidence: 99%